PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN MATERI PENGELOLAAN LINGKUNGAN DI SMP NEGERI 2 TANJUNG LAGO, KABUPATEN BANYUASIN - Irham Falahudin; Indah Wigati; Ayu Puji Astuti (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2016)
The study was based on a lack of learning processes that can enhance students' critical thinking skills. That is because the material presented is still conventional, and learning was dominated by the teacher, so the teacher-centered learning. The purpose of this study was to determine the effect of guided inquiry learning model to the students' critical thinking skills. This study was an experimental study using descriptive quantitative data analysis techniques. The instruments were the observation sheets, test and questionnaire. The data analysis used t-test, the data on the calculation the average difference obtained tcount both classes of 3.3849, while the 0,05 ttable at significant level of 1.684, so tcount > ttable, then H0 rejected and Ha accepted. Data from observations demonstrate critical thinking skills of students in the experimental class is higher than the control class that is 77%> 68%. Guided inquiry learning model has received positive responses to the responses of students strongly agree. Concluded that guided inquiry learning model on environmental management material effect on critical thinking skills of students at SMP 2 Tanjung Lago, Banyuasin.